2020
DOI: 10.1002/ped4.12202
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of cochlear implantation in children younger than 12 months of age

Abstract: Importance Cochlear implantation (CI) is an effective therapy for patients with severe to profound sensorineural hearing loss. It remains controversial whether children younger than 12 months of age should undergo CI. Objective To evaluate the safety and effectiveness of CI in children younger than 12 months of age. Methods We performed a retrospective study of clinical data of pediatric patients younger than 12 months of age who underwent CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 24 publications
0
20
0
2
Order By: Relevance
“…The 18 included studies involved a total of 449 pediatric patients 12 months and younger who underwent 625 cochlear implants (Table 1). 9,12,26,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Children ranged in age from 4 to 12 months across all studies. Information regarding laterality of cochlear implantation was included in 8 of 18 (44.4%) studies reported, with 124 implants being done on a single side and 89 being done bilaterally.…”
Section: Resultsmentioning
confidence: 99%
“…The 18 included studies involved a total of 449 pediatric patients 12 months and younger who underwent 625 cochlear implants (Table 1). 9,12,26,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Children ranged in age from 4 to 12 months across all studies. Information regarding laterality of cochlear implantation was included in 8 of 18 (44.4%) studies reported, with 124 implants being done on a single side and 89 being done bilaterally.…”
Section: Resultsmentioning
confidence: 99%
“…As a further consequence, one could also assume that frequent device use goes hand in hand with high device satisfaction. Currently, most studies concerning pediatric CI users have focused on assessing auditory skills and speech including verbal language ability or communication skills but never linked outcomes with quantitative device satisfaction and possibly related device use as well as device type dependency [ 4 , 8 , 13 , 27 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that early identification of hearing loss in children, e.g., through hearing screening programs, followed by timely and appropriate interventions can minimize developmental delays and facilitate communication, education, and social development [ 4 , 5 ]. Research suggests that children who are born deaf or acquire hearing loss very early in life and who receive appropriate interventions within six months of age are at par with their hearing peers in terms of language development by the time they reach the age of five years (in the absence of other impairments) [ 4 , 5 , 11 , 12 , 13 ]. However, surgery and CI adaptation alone do not guarantee the full benefit of its users.…”
Section: Introductionmentioning
confidence: 99%
“…Children with substantial congenital hearing impairment who receive cochlear implants at a younger age have better speech and language acquisition outcomes. 11 The auditory cortex has the most neural plasticity at birth, and this plasticity decreases over time. The critical period of learning and language development is within the first 3.5 years of life.…”
Section: Improving Outcomesmentioning
confidence: 99%